Clinical spectrum of severe acute malnutrition among children admitted to nutritional rehabilitation centre of a tertiary care hospital with special reference to incidence of bilateral pitting pedal oedema in children with severe acute malnutrition - Prashanth, M. R.; Savitha, M. R.; Raju, H. N. Yashwanth; Shanthi, M. (International Journal of Contemporary Pediatrics, 2018)
Background: Malnutrition is a major cause of morbidity and mortality in under five children globally, according to global nutrition report 2016, forty five percent of deaths in under five children are linked to malnutrition. The objective of this study was to study the clinical spectrum in children with Severe Acute Malnutrition (SAM) admitted to nutritional rehabilitation center of a tertiary care hospital. Methods: Children between the age group of 6 months to 5 years admitted in the nutritional rehabilitation centre during the period of 1 year (from April 2016 to March 2017) meeting our inclusion criteria were included in the study. We retrospectively reviewed the medical records of these children. Clinical spectrum of SAM was compared with comparison group. Results: A total of 100 cases were included in the study. Ninety five percent of children met the criteria of weight for height less than 3SD, 45% of children met the criteria of Mid Upper arm Circumference (MUAC) less than 11.5 cms and 5% of children met the criteria of bilateral pitting pedal oedema. Mean age of presentation of children in the present study was 15.8 months among which 45% were males and 55% were females. Major symptoms of the study group were fever, cough, hurried breathing, loss of appetite and loose stools with 79%, 45%, 27%, 26% and 23% as respective frequencies. Pneumonia (43%) was the major comorbidity among children admitted with severe acute malnutrition. Diarrhoea (21%), meningitis (8%), urinary tract infection (6%) were the other co-morbidities present in the study group. Conclusions: Pneumonia and diarrhoea are the major co-morbidities present in children with SAM. Majority of children fulfil the criteria of weight for height ≤3SD for diagnosis of SAM. There is a low incidence of oedematous malnutrition in the present study.